Identificación de las barreras de entrada de PyMEs a una red logística inversa de llantas usadas en la ciudad de Bogotá D.C. desde un enfoque de dinámica de sistemas (2018)
Obsolete products management is a complex and sometimes unattractive problem for organizations, due to the high degree of uncertainty regarding the materials’ return; high logistical costs invested during the collecting and disposal operations processes, and sometimes because the economical, legal and social advantages that can be achieved through the implementation of reverse logistics systems are ignored. This research focuses on the barriers of entry that an SME can experience when implementing or applying a reverse logistic system in Bogotá-Colombia. Through a System Dynamics model, causal relationships between variables were correlated, finding several limiting factors such as the market for those products derived from this process is not profitable and collection, transportation and treatment costs of these materials are not engaging for the main producer. On the other hand, production dynamics of tires in Bogotá is greater than the capacity of the available alternatives for use, thus it is necessary to promote new uses for the recovered materials including appealing offers for the producer in order to balance the system. This research represents significant contribution to build knowledge around application ranges of DS and provides relevant information for entrepreneurs and governmental bodies to direct in the decision-making seen from systemic approaches, linking operational, legal and economic issues.